The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.saa.2013.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Raman and infrared spectroscopic characterization of the phosphate mineral paravauxite Fe2+Al2(PO4)2(OH)2⋅8H2O

Abstract: We have undertaken a vibrational spectroscopic study of paravauxite the Siglo XX mine, Bustillo Province, northern of Potosí department, Bolivia. This mine is important source for rare and unusual secondary phosphate minerals and is the type locality for a number of rare phosphates such as vauxite, sigloite, metavauxite and for jeanbandyite. The chemical formula of the studied sample was determined as Fe(2+)(0.9)5, Al(0.07)Σ1.02 (Al)2.09 (PO4)1:97 (OH)1.98 · 7.90(H2O). The Raman spectrum is dominated by an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…0 0 2 ) S 0 . 9 9 8 Al(1)Al(2) Al 2.005 P (P 1.998 Si 0.002 ) S2 O 8 (OH) 2 ·8H 2 O, which is close to that reported by Frost et al (2013) for a paravauxite from the same locality: F e (Fe 2 + 0 . 9 5 Mn 2 + 0 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…0 0 2 ) S 0 . 9 9 8 Al(1)Al(2) Al 2.005 P (P 1.998 Si 0.002 ) S2 O 8 (OH) 2 ·8H 2 O, which is close to that reported by Frost et al (2013) for a paravauxite from the same locality: F e (Fe 2 + 0 . 9 5 Mn 2 + 0 .…”
Section: Discussionsupporting
confidence: 85%
“…2, Table 4). Frost et al (2013) reported the Raman and IR spectra for a paravauxite from the same locality as that used in this study. The Raman spectrum was dominated by an intense Raman band at 1020 cm À1 , assigned to the n 1 symmetrical stretching mode of the PO 4 3À group.…”
Section: 001mentioning
confidence: 99%
“…This range is assigned to the vibration of ʋ2 and ʋ4 PO 4 3-bending modes. It was reported by S. Elgharbi and H. Lefires when they work about Tunisian phosphate rock that the Raman bands at 582, 591 and 607 cm -1 are assigned to ʋ4 PO 4 3-and the bands at 431 and 435 cm -1 are due to the ʋ2 PO 4 3- [12,13]. Then, the work reported by Karampasa about calcium phosphate confirmed very well the results above [29].…”
Section: Raman Characterizationsupporting
confidence: 54%
“…The chemical composition was determined by energy disersive X-ray EDX analysis. For the TEM sample preparation, we employed the ultrasound vibration method [13]. The samples were immersed in ethanol solution and ultrasound vibration was applied to separate precipitates from the phosphate.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, Cu radiation (kCu = 1.5405 Å ) was used and the sample was scanned in a 2h range of 8-108.5°at a scanning rate of 0.015°/S. The crystalline size was determined from the characteristic peak at 2h = 67.1667°(corresponding to the 440 plane) using Scherrer formula (Frost et al 2013), crystalline size, nm = K k/W cos h, where K is the shape factor = 0.9, k = wavelength of the X-ray used (1.5405) and W = (Wb -Ws, width of peak at half-height at 2h = 33.5833) the difference of broadened profile width of the experimental sample and the standard width of reference Al 2 O 3 sample. The mean crystalline size was obtained to be 11.5 nm.…”
Section: Adsorbent Characterization By X-ray Diffractionmentioning
confidence: 99%